Cancer stem cells in glioma: challenges and opportunities - Wang, Jialiang; Ma, Yufang; Cooper, Michael K. (Translational Cancer Research; Vol 2, No 5 (October 04, 2013): Translational Cancer Research (Stem Cells in Cancer), 2013)
The discovery of cancer stem cells in glioma has created a paradigm shift in our understanding of this deadly disease. Glioma stem cells exhibit sustained self-renewal and potent tumorigenic potential and differ from their more differentiated progeny in response to current therapies. Recurrent disease is likely derived from glioma stem cells or progeny reprogrammed to gain stem cell-like phenotypes, indicating that the stem cell phenotype is a crucial therapeutic target. While debate over cancer stem cell and clonal evolution models persists, important knowledge has been gained over the past decade from glioma stem cells investigation and clinical impact is expected.